Disruptions of Daily Life : Japanese Literary Modernism in the World - Mitchell, Arthur M. (Book collections on Project MUSE., 2020)
"This book explores the mass media landscape of early 20th century in order to uncover the real-world subversive impact of formalist works by four major Japanese authors-Tanizaki Jun'ichirō, Yokomitsu Riichi, Kawabata Yasunari, and Hirabayashi Taiko. Through broad surveys of discourses surrounding daily life, the 1923 Great Kanto Earthquake, urban renaissance, and the sexological rhetoric of love and lust, this study locates ideologies of gender, ethnicity, and nation that flourished in the 1920s. Mitchell then shows how the narrative and linguistic strategies of modernist texts interrogated the innocence of this language, discursively displacing the authority of their claims and disrupting their hold upon people's imagined relationship to daily life. Mitchell elaborates an alternative modernism that challenges the primacy of the Western European model by locating modernist subversion within the local historical developments of I-novel reading practices, commodity culture, and the Great Kantō Earthquake. But the book also helps to expand modernism studies into a more translational dialogue by identifying how modernist texts themselves exposed the global epistemology of East vs. West. By rehabilitating the original nexus between literature and society, Mitchell revives and affirms the essential pedagogical function of modernist fiction to make us aware of how our realities are constructed, and thus how those realities can be changed"--